Exploring the Specialized Teaching Methods of Confucius Institute in Thailand Based on International Chinese Language Education - Xu, Shurou; Hu, Yong (Journal of Educational Research and Policies, 2025)
Confucius Institutes (CIs) are public welfare organizations established by China to promote Chinese language and culture. Compared with Confucius Academy, Confucius Institutes are smaller in scale and more flexible in form, usually relying on local schools, communities or enterprises to carry out language teaching and cultural exchange activities in a way that is closer to the public. According to statistics, there are about 550 Confucius Institutes and 1,172 Confucius Classrooms in primary and secondary schools in 162 countries around the world. Among them, Thailand has one of the highest densities of Confucius Institutes and Confucius Classrooms in the world. As the construction of the “the Belt and Road” has been steadily promoted, the demand for Chinese language talents in various countries has continued to grow, and learning Chinese has become the “just education demand” of people in many countries [1]. Since the 21st century, Chinese language education in Thailand has continued to develop and gradually become complete, and has been fully integrated into the Thai education system. The purpose of teaching Chinese as a foreign language is to cultivate students’ ability to communicate in Chinese [2]. Under the interaction of the three core driving forces, a “triple driving mechanism” has been formed to promote the development of Chinese language education in Thailand. As an important carrier of international Chinese language education, the Confucius Institute in Thailand needs to design localized teaching strategies that take into account the Thai cultural background and learners’ needs. International Chinese language teachers in Thailand also need to improve their cross-cultural teaching skills. At the same time, with the maturity of AIGC technologies such as ChatGPT, DeepSeek, Doubao, etc., Thai Confucius Institutes are combining with them to innovate their teaching modes and improve teaching efficiency and learning experience. This paper takes the Confucius Institute in Thailand as the research object, and analyzes the challenges and opportunities it faces in the process of teaching by combining the theory and practice of international Chinese education. Through the research on the Thai Chinese education system, learners’ characteristics, and teaching resources allocation, it puts forward targeted teaching method optimization strategies to provide reference for improving the quality of Chinese education in Thailand.